2019
DOI: 10.3892/etm.2019.7812
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‑548b inhibits proliferation and invasion of hepatocellular carcinoma cells by directly targeting specificity protein�1

Abstract: Emerging studies have revealed that microRNAs (miRNAs) are aberrantly expressed in hepatocellular carcinoma (HCC), and the dysregulation of miRNAs exerts crucial roles in the carcinogenesis and development of HCC. Therefore, elucidating the relationship between miRNAs and HCC progression is of great importance to develop novel therapeutic techniques and to improve the prognosis of patients with this malignancy. Recently, miR-548b-3p (miR-548b) has been demonstrated to be a cancer-associated miRNA in tongue squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…25 miR-548b is also expressed at a low level in HCC tissues and might serve as a tumor-suppressive miRNA in proliferation and invasion of HCC cells. 26 Nevertheless, the potential mechanisms behind miR-548b in regulation of melanoma development need to be deeply explored. HMGB1 is a nuclear nonhistone protein and implicated in cancerogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…25 miR-548b is also expressed at a low level in HCC tissues and might serve as a tumor-suppressive miRNA in proliferation and invasion of HCC cells. 26 Nevertheless, the potential mechanisms behind miR-548b in regulation of melanoma development need to be deeply explored. HMGB1 is a nuclear nonhistone protein and implicated in cancerogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, accumulating evidence has demonstrated the key roles of miRNAs in the progression of liver cancer by acting as tumor suppressors or oncogenes (11). For example, miR-548b suppresses the proliferation and invasion of liver cancer cells by targeting specificity protein 1 (12). Previous studies have revealed that miR-574-3p acts as a tumor suppressor in numerous types of cancer (13)(14)(15)(16)(17), such as esophageal squamous cell carcinoma (ESCC), in which miR-574-3p is downregulated and may be a predictor of the postoperative outcome of patients with ESCC (13).…”
Section: Introductionmentioning
confidence: 99%
“…The miR-548b inhibits cells proliferation and enhances apoptosis in breast cancer [38]. The miR-548b also inhibits proliferation and invasion in malignant glioma [39] and hepatocellular carcinoma (HCC) [40,41]. On the other hand, in esophageal squamous cell carcinoma (ESCC), the miR-548 enhances cell migration and invasion [42].…”
Section: Discussionmentioning
confidence: 99%